The Influence of Mechanical Activation on the Structure of a ZrO[2(MgO) Nanocrystalline Powder; AIP Conference Proceedings; Vol. 2051 : Advanced Materials with Hierarchical Structure for New Technologies and Reliable Structures 2018 (AMHS’18) - Mirovoy Yu. A. Yury Aleksandrovich; Gusev A. Yu.; Buyakov A. S. Ales Sergeevich; Burlachenko A. G.; Buyakova S. P. Svetlana Petrovna (2018, 2018)
Title screen